Next generation sequencing in patients with nephrolithiasis: how does it perform compared with standard urine and stone cultures?. (February 2021) - Nottingham, Charles U.; Assmus, Mark A.; Peters, Alexander W.; Large, Tim; Agarwal, Deepak K.; Rivera, Marcelino E.; Krambeck, Amy E.
Background: Our aim was to compare microorganism detection between standard culture (Ctx) and next generation sequencing (NGS) in patients undergoing surgery for nephrolithiasis; we prospectively compared both urine and stone culture results using these two techniques. Methods: We prospectively compared microorganism detection of urine and stone cultures using Ctx versus NGS in patients undergoing surgery for nephrolithiasis. We analyzed preoperative voided urine (Voided) using both Ctx and NGS. Intraoperatively, renal stone (Stone) cultures were analyzed with Ctx and NGS. The primary outcome was concordance in microorganism detection between Voided Ctx and Stone NGS, as well as between Stone Ctx and Stone NGS. Results: We prospectively evaluated 84 patients. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of Voided Ctx predicting Stone Ctx were 66.7%, 73.7%, 54.5%, and 82.4%, respectively. Concordance of Voided Ctx microorganisms to Stone microorganisms decreased when NGS was used for the Stone compared with Ctx. The sensitivity, specificity, PPV, and NPV of Voided NGS to predict Stone Ctx microorganisms were 85.2%, 24.6%, 34.8%, and 77.8%, respectively. The concordance of Voided NGS to Stone microorganisms improved when the Stone was analyzed via NGS compared with Ctx. Conclusion: NGS has a higher detection rate of microorganisms than standard culture for both preoperative urine and stone cultures. Voided NGS was the most sensitive in predicting a positive Stone sample, but the specificity and PPV were, overall, low. Further correlation of NGS microorganism detection with patient outcomes will determine which clinical situations may benefit most from NGS versus standard culture in patients with urinary-tract stones.